Subjektivitet og narrativitet - Zahavi, Dan (K&K - Kultur og Klasse, 2006)
Subjectivity and narrativity If the self – as a popular view has it – is a narrative construction, if it arises out of discursive practices, it is reasonable to assume that the best possible avenue to self-understanding will be provided by those very narratives. If I want to know what it means to be a self, I should look closely at the stories that I and others tell about myself, since these stories constitute who I am. In the following I wish to question this train of thought. I will argue that we need to operate with a more primitive and fundamental notion of self; a notion of self that cannot be captured in terms of narrative structures. In a parallel move, I will argue that there is a crucial dimension of what it means to be ‘other’ that is equally missed by the narrative approach. I will consequently defend the view that there are limits to the kind of understanding of self and others that narratives can provide.